Penerapan Konsep-Konsep Digitalisasi dalam Pelayanan Publik di Kantor Desa Manunggal Jaya Kecamatan Tenggarong Seberang Kabupaten Kutai Kartanegara - Deandlles Christover; Aji Syarif Hidayattulah; Indah Mawarni (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Digitization is the process of converting information or data from a physical form into a digital format that can be processed using information technology. In an effort to improve the quality of public services, the government needs to utilize various online platforms such as websites, mobile applications and social media. This step aims to strengthen the E-Government system and facilitate public access to information and services provided by the government. Thus, digitization plays an important role in advancing public services and increasing interaction between government and society. The purpose of this study was to find out how the application of the concept of digitization in public services at the Manunggal Jaya Village Office. This study uses qualitative research methods aimed at describing, summarizing the various conditions, situations or variables studied. Data collection was carried out through interviews, observation, and literature studies. The data collection techniques are purposive sampling and accidental sampling. The research focus includes elements of support, capacity, benefits, as well as supporting and inhibiting factors in implementing the concept of digitalization. The results of the study show that as a form of implementing the digitalization concept, Manunggal Jaya Village has developed and activated an official website as an effort to improve the quality of public services. However, the obstacles found were the lack of public knowledge about the Village website and low participation in accessing it. For this reason, wider socialization and education that is directed to the community is needed regarding the use of the Village website.